Directional auxin transport mechanisms in early diverging land plants - Viaene, Tom; Landberg, Katarina; Thelander, Mattias; Medvecka, Eva; Pederson, Eric; Feraru, Elena; Cooper, Endymion D; Karimi, Mansour; Delwiche, Charles F; Ljung, Karin; Geisler, Markus; Sundberg, Eva; et al. (Current biology, 2014)
The emergence and radiation of multicellular land plants was driven by crucial innovations to their body plans. The directional transport of the phytohormone auxin represents a key, plant-specific mechanism for polarization and patterning in complex seed plants. Here, we show that already in the early diverging land plant lineage, as exemplified by the moss Physcomitrella patens, auxin transport by PIN transporters is operational and diversified into ER-localized and plasma membrane-localized PIN proteins. Gain-of-function and loss-of-function analyses revealed that PIN-dependent intercellular auxin transport in Physcomitrella mediates crucial developmental transitions in tip-growing filaments and waves of polarization and differentiation in leaf-like structures. Plasma membrane PIN proteins localize in a polar manner to the tips of moss filaments, revealing an unexpected relation between polarization mechanisms in moss tip-growing cells and multicellular tissues of seed plants. Our results trace the origins of polarization and auxin-mediated patterning mechanisms and highlight the crucial role of polarized auxin transport during the evolution of multicellular land plants.